T-Cell Subpopulations and Differentiation Bias in Diabetic and Non-Diabetic Patients with Chronic Kidney Disease - Ana Cecilia Granda Alacote; Gabriela Goyoneche Linares; María Gracia Castañeda Torrico; Daysi Zulema Diaz-Obregón; Michael Bryant Castro Núñez; Alexis Germán Murillo Carrasco; Cesar Liendo Liendo; Katherine Susan Rufasto Goche; Víctor Arrunátegui Correa; Joel de León Delgado (Biomedicines)
Background: Chronic kidney disease (CKD) patients often experience dysregulated inflammation, particularly when compounded by comorbidities such as type 2 diabetes (T2D). Objective: The aim of this study was to determine whether T2D influences the profile of memory T lymphocytes, regulatory T cells (Tregs), and the gene expression of transcription factors such as T-bet (Tbx21), GATA3, RORyT (RORC), and FOXP3 in CKD patients. Methods: Twenty-two CKD patients undergoing hemodialysis were selected for the study. Flow cytometry was used to identify naïve T cells, Tregs (CD4+CD25+CD127-), central memory T lymphocytes (CCR7+CD45RA-), effector memory T lymphocytes (CCR7-CD45RA-), and TEMRA cells (CCR7-CD45RA+). The expression of helper T cell differentiation regulatory genes was assessed using real-time RT-PCR. Results: Both helper and cytotoxic effector memory T cell populations were found to be higher than naïve lymphocytes in CKD patients, regardless of T2D status. However, Tregs were significantly more frequent in diabetic CKD patients (5.1 ± 2.6%) compared to non-diabetic patients (2.8 ± 3.1%). In terms of transcription factor expression, a significant correlation was observed between T-bet and FOXP3 in diabetic patients, and between RORyT and FOXP3 in non-diabetic patients. Conclusions: While T2D does not notably alter the distribution of memory T cells in CKD patients, it significantly impacts the frequency of Tregs and their correlation with pro-inflammatory transcription factors like T-bet (Tbx21) and RORyT.